Pre-exposure prophylaxis of non-HIV viral infections and the role of long-acting antivirals - Soriano, Vicente; Moreno-Torres, Víctor; de Mendoza, Carmen; Fernández-Montero, José V; Treviño, Ana; Corral, Octavio; de Jesús, Fernando; Barreiro, Pablo (AIDS Review, 2025)
Viruses cause a large burden of human infectious diseases. During the past 50 years, antivirals have been developed to treat many pathogenic viruses, including herpesviruses, retroviruses, hepatitis viruses, and influenza. Besides being used as treatment, antivirals have shown efficacy for preventing certain viral infections. Following the success in the HIV field, a renewed interest has emerged on the use of antivirals as prophylaxis for other viruses. The development of formulations with extended half-life has pushed further this consideration in persons at risk for a wide range of viral infections. In this way, long-acting antivirals might behave as "chemovaccines" when classical vaccines do not exist, cannot be recommended, immune responses are suboptimal, escape mutants emerge, and/or immunity wanes. Five main caveats would temper its use, namely, selection of drug resistance, drug interactions, short- and long-term side effects, potential teratogenicity in women of child-bearing age, and high cost. Herein, we discuss the prospects for long-acting antivirals as prophylaxis of human viral infections other than HIV.
Keywords: antiviral therapy; cytomegalovirus; hepatitis B; hepatitis C; human T-cell lymphotropicvirus type 1; pre-emptive therapy; pre-exposure prophylaxis; prophylaxis; SARS-CoV-2